2019
DOI: 10.3390/cancers11101461
|View full text |Cite
|
Sign up to set email alerts
|

Arl13b Regulates Breast Cancer Cell Migration and Invasion by Controlling Integrin-Mediated Signaling

Abstract: Breast cancer is the first cause of cancer-related mortality among women worldwide, according to the most recent estimates. This mortality is mainly caused by the tumors’ ability to form metastases. Cancer cell migration and invasion are essential for metastasis and rely on the interplay between actin cytoskeleton remodeling and cell adhesion. Therefore, understanding the mechanisms by which cancer cell invasion is controlled may provide new strategies to impair cancer progression. We investigated the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Recently, our group found evidence that ARL13B plays a role in breast tumorigenesis and cancer progression, likely independently of cilia. Indeed, depletion of ARL13B in breast cancer cells leads to a reduction in cell migration and invasion in vitro and impaired tumor progression in vivo (Casalou et al, 2019). Moreover, our results revealed a new mechanism to explain the role of ARL13B in tumor progression, through the modulation of cell-ECM adhesion and integrin-mediated signaling.…”
Section: Arl13bmentioning
confidence: 62%
See 2 more Smart Citations
“…Recently, our group found evidence that ARL13B plays a role in breast tumorigenesis and cancer progression, likely independently of cilia. Indeed, depletion of ARL13B in breast cancer cells leads to a reduction in cell migration and invasion in vitro and impaired tumor progression in vivo (Casalou et al, 2019). Moreover, our results revealed a new mechanism to explain the role of ARL13B in tumor progression, through the modulation of cell-ECM adhesion and integrin-mediated signaling.…”
Section: Arl13bmentioning
confidence: 62%
“…In the same study, we found that NMIIA mediates ARL13B binding to actin and that both proteins are required for the formation of circular dorsal ruffles (CDRs), which are actin-rich structures required for cell migration (Casalou et al, 2014). Our group also found that GTP-bound ARL13B interacts with NMIIA in breast cancer cells (Casalou et al, 2019). Other studies reported the role of NMIIA in different types of cancers and indicate that NMIIA can function as a tumor suppressor or oncogene.…”
Section: Arl13bmentioning
confidence: 64%
See 1 more Smart Citation
“…ARL13B was also involved in the GBM development, and the protein level of ARL13B was higher in tumor samples than in normal samples. Casalou et al con rmed that breast cancer was promoted by ARL13B, which was connected with cancer cell migration and invasion [36]. Another gene, SETDB1 regulated histone methylation, gene silencing, and transcriptional repression [37].…”
Section: Discussionmentioning
confidence: 99%
“…ARL4A could interact with Robo1 to promote cell migration by activating Cdc42 (10). A recent study reveals that ARL13B can enhance the migration and invasion of breast cancer cells via controlling integrin-mediated signaling pathway (11). Moreover, ARL4C overexpression promotes the progression of glioblastoma (GBM) in vitro and in vivo and indicates the poor prognosis for patients with GBM (12).…”
Section: Introductionmentioning
confidence: 99%